Structural Decomposition Analysis of CO2 Emission Reduction due to Energy Tax in Power Sector Planning - Marpaung, Charles O. P.; Shresta, Ram M. (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
This study analyses the CO2 emission implications of considering energy tax in power sector planning for the case of Indonesia. There are four energy tax rates considered in this study i.e. US$0.5/MBtu, US$1.0/MBtu, US$2.0/MBtu and US$5/MBtu. Furthermore, this study also analyses the decomposition of the economy-wide CO2 emission changes due to the carbon tax rates by using an input-output model. The implications of energy tax on utility planning would bring the sytem more efficient because more energy efficient technology power plants, such as CCGT, would be selected, while in the case of environmental implications, CO2 emissions would be reduced. The results show that there is a significant change in the annual CO2 emissions if energy tax rate of US$5/MBtu is introduced. There are three major components that affect the total economy-wide change in CO2 emissions, i.e., fuel mix-, structural-, and final demand- effects. The results show that the fuel mix effect is found to be most influential in reducing the CO2 emission during the planning horizon under all of the energy tax rates considered and is followed by the final demand- and structural-effects.